Hierarchical framework of collaborative 3D semantic mapping based on semantic segmentation - Li, Ruilin (2019)
In recent years, significant progress has been made in semantic segmentation and 3D geometric mapping. As a result, multi-robot systems are expected to operate in increasingly complex environment with intelligent ability, such as dynamic perception and active navigation. In this case, comprehensive contextual understanding of the surroundings is a critical challenge for multi-robot perception system. Attempts have been made from single robot semantic mapping, collaborative 3D geometric mapping. However, there is a gap in performing accurate and largescale semantic mapping for multiple robots. This thesis goes a step further by focusing on a hierarchical multi-robot semantic mapping framework.